Pengaruh Latihan Daya Tahan Kekuatan Otot Lengan Terhadap Banyaknya Pukulan Uppercut Atlet Wushu Sanda Club Unpatti - Indayani, Ainun Ha; Fenanlampir, Albertus (MANGGUREBE: Journal Physical Education, Health and Recreation, 2023)
Based on the results of hypothesis, it is known that there is an influence of arm muscle strength endurance training on the number of uppercut at Unpatti Wushu Club Athletes. This training process for 6 weeks with a training frequency of 3 times a week, so that the total training process for 15 athletes were 18 times. From the length of the process, it is known that the planned training program can improve the results of Uppercut hitting ability as proven statistically, namely t-count = -8.282 and compared with the t-table value on dk/df N-1 (15-1 = 14) of 2.145. Thus it can be understood t-count > t-table. This shows that there is a very significant influence of arm muscle endurance training on the number of uppercuts in Unpatti Wushu Club Athletes. These results can be achieved through planning an objective and systematic training program based on the abilities of Unpatti wushu club athletes.